Does Risk Management Affect on Bank Efficiency? An Analysis of Sri Lankan Banking Sector (International Journal of Management and Sustainability, 2014)
Increasing competition in the finance sector in Sri Lank has created a huge competition among the banking sector. The high level of competition improved the bank efficiency and efficiency creates risk to the banks. Therefore, risk management is a vital in achieving efficiency. Therefore, this study addresses the question on “whether the Sri Lankan banks are efficient and how risk management improves the banks’ efficiency?. The main objective of the study was to identify the efficiency of the banks by incorporating risk factors. This study adopted second Stage Data Envelopment Analysis based on Licensed Domestic Commercial Banks in Sri Lanka for the period from 2005 to 2011. At the first stage it use DEA to finds the efficiency scores by incorporating risk factors such as Credit, Market and Operational risk. In the second stage it applies Tobit regression to find the influence of external environment factors on bank efficiency. The mean efficiency of Sri Lankan banks is high when it compares with the other well countries such as India, UK, US, Taiwan and Islamic Banks located in London. Risk management has improved the efficiency of the Licensed Commercial Banks in Sri Lanka. Therefore, banks should identify their standing on the market on efficiency levels and should analyze their inefficiencies to improve the efficiencies further.